Targeting the “cytokine storm” for therapeutic benefit - D'Elia, RV; Harrison, K; Oyston, PC; Lukaszewski, RA; Clark, GC (American Society for Microbiology, 2013)
Inflammation is the body's first line of defense against infection or injury, responding to challenges by activating innate and adaptive responses. Microbes have evolved a diverse range of strategies to avoid triggering inflammatory responses. However, some pathogens, such as the influenza virus and the Gram-negative bacterium Francisella tularensis, do trigger life-threatening “cytokine storms” in the host which can result in significant pathology and ultimately death. For these diseases, it has been proposed that downregulating inflammatory immune responses may improve outcome. We review some of the current candidates for treatment of cytokine storms which may prove useful in the clinic in the future and compare them to more traditional therapeutic candidates that target the pathogen rather than the host response.